Does a social self‐perceptual bias mask internalizing symptoms in children with attention‐deficit/hyperactivity disorder?. (26th February 2019) - Martin, Caroline P.; Peisch, Virginia; Shoulberg, Erin K.; Kaiser, Nina; Hoza, Betsy
Abstract : Background: Children with attention‐deficit/hyperactivity disorder (ADHD) often present with additional psychiatric conditions. Comorbidity is associated with poorer long‐term outcomes, highlighting the need for effective assessment and intervention. However, self‐perceptual biases may mask the presence of symptoms for a subgroup of children with ADHD. This study examined the role of social self‐perceptual biases in children with ADHD versus control children on self‐reports of loneliness, and depressive and anxious symptoms. Methods: The research question was examined in two samples. Sample 1 consisted of 7.7–12.8‐year‐old boys with ADHD ( n  =   199) and control boys ( n  =   74); Sample 2 consisted of 7.7–11.4‐year‐old boys and girls with ADHD ( n  =   178) and control children ( n  =   86). Across samples, children reported social competence and symptoms of anxiety and depression. Child‐reported loneliness was examined in Sample 1. A social competence discrepancy score (difference between self‐report and teacher‐report) was used as an indicator of social self‐perceptual bias. Results: Hierarchical multiple regression analyses tested social self‐perceptual bias as a suppressor variable. The magnitude of the associations between ADHD and self‐reported feelings of depression, anxiety and loneliness was greater when social self‐perceptual bias was included in models as compared to models that did not include social self‐perceptual bias (Δ R 2 s range = 0.04–0.19). Conclusions: Findings across both samples suggest that social self‐perceptual biases may mask internalizing symptom severity on self‐reports for individuals who overestimate their social competence. More research is needed to determine the best approach to assessing internalizing problems among children with ADHD.